Assessment of Pharmacological Management of Acute Watery Diarrhea in Pediatric Patients: A Collaborative Study Between the Departments of Pharmacology and Pediatrics at a Tertiary Care Hospital (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Acute watery diarrhea (AWD) is a leading cause of morbidity and mortality among children under five, especially in low- and middle-income countries like Bangladesh. Effective management with oral rehydration solution (ORS) and zinc supplementation is critical to reduce complications and improve recovery. This study aimed to assess pharmacological management practices for pediatric AWD, including adherence to guideline- based therapy, use of ORS, zinc, adjunct therapies, and antibiotics.Methods: A descriptive, observational study was conducted at Community Based Medical College, Bangladesh, from January to December 2025. A total of 167 children aged 6 months to 12 years with AWD were enrolled. Data on demographics, clinical features, pharmacological management, and outcomes were collected using a structured questionnaire and review of medical records. Data were analyzed with SPSS version 25 using descriptive statistics and chi-square tests.Results: Of the 167 patients, 95 (56.9%) were male and 72 (43.1%) female, with the majority aged 1–5 years (53.9%). Mild to moderate dehydration was observed in 74.8% of cases. ORS was administered to 160 patients (95.8%) and zinc to 145 (86.8%). Antibiotics were prescribed in 110 cases (65.9%), predominantly ciprofloxacin (45.5%) and azithromycin (31.8%). Adjunct therapies such as antiemetics and recontrol were used less frequently. Clinical outcomes were favorable: 150 patients (89.8%) recovered fully, 12 (7.2%) recovered with minor complications, and 5 (3%) were referred or did not recover.Conclusion: Guideline-based management with ORS and zinc resulted in high recovery rates among pediatric AWD patients. Challenges remain regarding unnecessary antibiotic use and underutilization of adjunct therapies. Reinforcing rational pharmacological practices is essential to optimize outcomes and reduce the burden of pediatric diarrhea in Bangladesh.Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 21-26